2022
DOI: 10.3390/molecules27092851
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Anti-Neuroinflammatory Inhibitors from Antarctic Fungal Strain Aspergillus sp. SF-7402 via Regulating the NF-κB Signaling Pathway in Microglia

Abstract: Microglia play a significant role in immune defense and tissue repair in the central nervous system (CNS). Microglial activation and the resulting neuroinflammation play a key role in the pathogenesis of neurodegenerative disorders. Recently, inflammation reduction strategies in neurodegenerative diseases have attracted increasing attention. Herein, we discovered and evaluated the anti-neuroinflammatory potential of compounds from the Antarctic fungi strain Aspergillus sp. SF-7402 in lipopolysaccharide (LPS)-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Compound methyl rosmarinate was identified at m/z 374, as previously reported in E. tinifolia ethyl acetate portion [26], and was known for its antioxidant and antifungal activities [22,27]. For the identification of the remaining compounds, the m/z values of the molecular ion [M-H] − and [M + HCOO] − were compared with the Waters Unifi Software Traditional Medicine Library (Waters Corporation, Milford, MA, USA) and corroborated from the previously reported literature [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Among these compounds, schisantherin A, kaempferol-3,7diglucoside, procyanidin A2, and tocopherol exert anti-inflammatory and antioxidant activity and promote reproductive functions [43][44][45][46], which explain the potent antioxidant and anti-inflammatory activity observed in E. tinifolia.…”
Section: Rosmarinic Acid Is a Major Consituent Of Etmementioning
confidence: 60%
“…Compound methyl rosmarinate was identified at m/z 374, as previously reported in E. tinifolia ethyl acetate portion [26], and was known for its antioxidant and antifungal activities [22,27]. For the identification of the remaining compounds, the m/z values of the molecular ion [M-H] − and [M + HCOO] − were compared with the Waters Unifi Software Traditional Medicine Library (Waters Corporation, Milford, MA, USA) and corroborated from the previously reported literature [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Among these compounds, schisantherin A, kaempferol-3,7diglucoside, procyanidin A2, and tocopherol exert anti-inflammatory and antioxidant activity and promote reproductive functions [43][44][45][46], which explain the potent antioxidant and anti-inflammatory activity observed in E. tinifolia.…”
Section: Rosmarinic Acid Is a Major Consituent Of Etmementioning
confidence: 60%
“…Both compounds inhibited NO production by down-regulating the expression of inducible nitric oxide synthase (iNOS) and also reduced the nuclear translocation of NF-κB. These experimental results suggested that these two compounds are promising candidates for the treatment of neuroinflammatory diseases [ 60 ].…”
Section: Biosynthesis Structural and Biological Activity Studiesmentioning
confidence: 99%